Digitalisasi Proses Pendaftaran, Bimbingan, dan Sidang Kerja Praktek - Sulaeman Santoso; Erico Darmawan Handoyo; Christian Chastro (Universitas Multimedia Nusantara, 2020)
The Recent Covid Pandemic has brought to realization that more than ever digitalization of manual labor is of the utmost importance. Changes from manual processes to an automated process through software medium however often times resulted in several drawbacks. One of which is when the actual process being digitalized undergoes major changes then the software would have to be revised. This is the case for the website for registering internship. This research digitalizes a lot of previously still manual processes and applies changes in the process for registering, working, and grading internship program.